2016
DOI: 10.1111/1365-2664.12747
|View full text |Cite
|
Sign up to set email alerts
|

High cover of hedgerows in the landscape supports multiple ecosystem services in Mediterranean cereal fields

Abstract: Field-margin diversification through conservation and restoration of hedgerows is becoming a prominent intervention for promoting biodiversity and associated ecosystem services in intensive agricultural landscapes. However, how increasing cover of hedgerows in the landscape can affect ecosystem services has rarely been considered.\ud Here, we assessed the effect of increased field-margin complexity at the local scale and increasing cover of hedgerows in the landscape on the provision of pest control, weed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 68 publications
3
85
1
2
Order By: Relevance
“…In simplified landscapes where flower-rich habitats have been lost, an effective solution could instead be the adoption of complementary interventions aiming to enhance FRs. The establishment of wildflower strips (Scheper et al, 2015) or hedgerows (Dainese, Montecchiari, Sitzia, Sigura, & Marini, 2017;Dainese, Riedinger et al, 2017;Morandin & Kremen, 2013) is, for instance, a simple strategy to create high-quality habitats taking little or no land from crop production. These interventions should be targeted at providing continuous bloom over the season for supporting the greatest diversity of wild pollinators (Scheper et al, 2015;Williams et al, 2015;Wood, Holland, & Goulson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In simplified landscapes where flower-rich habitats have been lost, an effective solution could instead be the adoption of complementary interventions aiming to enhance FRs. The establishment of wildflower strips (Scheper et al, 2015) or hedgerows (Dainese, Montecchiari, Sitzia, Sigura, & Marini, 2017;Dainese, Riedinger et al, 2017;Morandin & Kremen, 2013) is, for instance, a simple strategy to create high-quality habitats taking little or no land from crop production. These interventions should be targeted at providing continuous bloom over the season for supporting the greatest diversity of wild pollinators (Scheper et al, 2015;Williams et al, 2015;Wood, Holland, & Goulson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several recent studies did not report an increased diversity of flower-visiting insects with such a mixture, recalling that a high functional diversity at the mixture level does not necessarily enhance insect diversity (Balzan et al, 2014(Balzan et al, , 2016aHatt et al, 2017c;Uyttenbroeck et al, 2017). At the landscape scale, however, the increased density of flowering features such as hedgerows showed a positive effect on pest control by parasitoids and pollination (Dainese et al, 2017).…”
Section: Pollinationmentioning
confidence: 93%
“…Finally, Sarthou et al (2014) observed that the local habitat structure (especially of grass strips), rather than landscape complexity, affects abundance of a diversity of natural enemies at emergence (i.e. after overwintering period) while Dainese et al (2017) reported that the increased cover of hedgerows at the landscape scale increased aphid parasitism independently from margin diversity at the local scale. This variability of results in the interaction between local and landscape scales may be explained by the diversity of natural enemies, pests and crops studied.…”
Section: Interactions Between Local and Landscape Scalementioning
confidence: 99%
“…physiographic units, landscape units, geomorphologic units, geological units, iso‐slope zones, agricultural units, and road‐bounded areas), in this model the discretization methodology based on administrative boundaries makes it possible to obtain data from databases of agricultural production or other supports, such as regional technical maps and ortho‐photo images. Image processing for the classification of high‐resolution satellite images could also be used for this purpose …”
Section: Methodsmentioning
confidence: 99%